Optimalisasi Urban Farming Menggunakan Botol Bekas Sebagai Strategi Peningkatan Ketahanan Pangan Di Kecamatan Cipayung, Jakarta Timur - Sitohang, Ester Juliana; Ana, Ayu Putri; Alfikri, M Reza; Mulyanti, Dwi Retno; Sitohang, Indah Grasulina (Pencerah, 2023)
The community service that has been implemented in Lubang Buaya Village, Cipayung District, in 2023, aims to stimulate the use of used bottles as an innovative solution in overcoming the food crisis and strengthening local food security. This effort is in line with government initiatives to develop domestic food security and reduce dependence on food supplies from abroad. In addition, research and development related to urban farming practices using used bottles in Cipayung plays an important role in providing practical guidance to local communities to start and run urban farming practices effectively. This step is expected to help city residents produce their own food sustainably, reduce the burden of food imports, and improve community food security. Throughout the program, a continuous evaluation phase has also been conducted. This allows monitoring the long-term impact of this activity, including the improvement of the quality of life of the local community. In conclusion, this community service program has successfully improved participants' knowledge, skills, and insights related to the basic principles of hydroponic plant cultivation. It has also stimulated business development on a household scale and contributed to the improvement of the surrounding environment.